Lamellar keratoplasty using femtosecond laser intrastromal lenticule for limbal dermoid: case report and literature review. Issue 11 (November 2018) - Pant, Om Prakash; Hao, Ji-long; Zhou, Dan-dan; Wang, Fan; Zhang, Bing-jie; Lu, Cheng-wei
Small incision refractive lenticule extraction (SMILE) is a femtosecond laser technique to correct myopia and myopic astigmatism. Herein, we report a technique where intrastromal lenticule obtained from the SMILE procedure served as a graft for lamellar keratoplasty in the management of a limbal dermoid. An 18-year-old woman presented to the clinic with a corneal-limbal mass in the right eye. Slit-lamp examination revealed a vascularized circular mass of approximately 6 mm × 5 mm, which was attached at 7 o'clock in the inferotemporal region of the corneal limbus; this suggested limbal dermoid. Anterior segment optical coherence tomography revealed superficial involvement of the cornea. The patient was treated with excision and lamellar keratoplasty by using femtosecond intrastromal lenticule. The lenticule was sutured over the cornea with 10-0 interrupted nylon sutures. On postoperative follow-up, best-corrected visual acuity was 20/20; there was no corneal neovascularization and no sign of rejection. This case of limbal dermoid was managed by simple surgical excision and lamellar keratoplasty with a SMILE-extracted lenticule. This method may serve as an alternative surgical approach for management of limbal dermoid.